Masticatory motion after surgical or nonsurgical treatment for unilateral fractures of the mandibular condylar process - Throckmorton, Gaylord S; Ellis, Edward; Hayasaki, Haruaki (Journal of oral and maxillofacial surgery, 2004)
We sought to compare mandibular motion during mastication in patients treated in either an open or a closed fashion for unilateral fractures of the mandibular condylar process. Eighty-one male patients with unilateral condylar process fractures were treated either with (n = 37) or without (n = 44) surgical reduction and rigid fixation of their condylar process fractures. At 6 weeks, 6 months, 1 year, and 2 years after treatment, the subjects’ chewing cycles were recorded using a magnetic sensor array (Sirognathograph; Siemens Corp, Bensheim, Germany) while chewing Gummi-Bears (HARIBO, Bonn, Germany) unilaterally on the same side as the fracture and on the opposite side. The chewing cycles were analyzed using a custom computer program, and the duration, excursive ranges, and 3-dimensional cycle shape were compared between the 2 treatment groups at each time interval using multilevel linear modeling statistics. The 2 treatment groups did not differ significantly for any measure of cycle duration or any excursive range (except lateral excursions at 1 year post-treatment) at any of the time intervals. However, the 3-dimensional cycle shapes of the 2 groups did differ significantly at all time intervals. Surgical correction of unilateral condylar process fractures has relatively little effect on the more standard measures (duration and excursive ranges) of masticatory function. However, surgical correction better normalizes opening incisor pathways during mastication on the side opposite the fracture.